Enhancement of physical properties of sugar palm (arenga pinnata merr.) fibre-reinforced unsatured polyester composite via vacum resin impregnation - Ishak, Mohamad Ridzwan (2012)
This research was carried out to study the enhancement of properties of sugar palm (Arenga pinnata) fibre reinforced unsaturated polyester composites. The study was divided into three stages, where the first stage focused on the characterization of tensile, chemical properties, thermogravimetric analysis (TGA) and Fourier transform infrared (FT-IR) spectra of the sugar palm fibers obtained from different heights (1,3, 5, 7, 9, 11, 13 and 15 m) of a sugar palm tree. It was observed that the fibers obtained from dead palm frond region showed the lowest tensile properties and considered to be biologically egraded. Chemical analysis of the fibers showed that the content of cellulose, hemicelluloses and lignin had a direct relationship to the increase in tensile strength, elongation at break and modulus of the fiber respectively. The second stage of the study investigated the effects vacuum resin impregnation on physical and mechanical properties of the sugar palm fibers. The fibers were impregnated with two different impregnation agents: phenol formaldehyde (PF) and unsaturated polyester (UP) at a constant pressure of 1000 mmHg at different impregnation times (0, 5, 10, 15, 20 and 25 minutes). Both physical and mechanical properties of the fibers showed significant improvement after being impregnated for 5 minutes and no improvement when impregnation time was extended from 10 to 25 minutes. The study further investigated the effects of elevating impregnation pressure (1000, 900, 800, 700, 600 and 500 mmHg) on physical and mechanical properties of sugar palm fiber with PF and UP at constant impregnation time of 5 minutes. It was observed that the moisture content (MC) of the impregnated fibers dropped from 8.19% to 0.75-0.46% for PF and 0.87-0.44% for UP, while the water absorption (WA) was reduced from 116.82% to 61.64-22.52% for PF and 63.49-23.31% for UP.The tensile strength increased from 243.77 MPa to 251.39-297.67 MPa for PF and 287.84-344.71 MPa for UP. The tensile moduli increased from 3.07 GPa to 3.1-3.98 GPa for PF and 3.15-3.98 GPa for UP. The elongation at break decreased from 25.16% to 17.66-6.26% for PF and 24.24-19.05% for UP. Low tensile strength and elongation at break of PF-impregnated fibers showed that the fibers were inferior in toughness (48.51 MJ/m3 to 33.08-12.29 MJ/m3) compared to UP-impregnated fibers (48.51 MJ/m3 to 57.56-45.21 MJ/m3). The third stage was continued by impregnating the fibers with UP resin at impregnation pressure of 600 mmHg for 5 minutes. The inter-facial shear strength (IFSS), TGA and FT-IR spectra of UP-impregnated sugar palm fiber were initially determined before the fibers were used as reinforcement in composites at 10, 20, 30, 40 and 50% fiber loading. It was observed that the impregnation process increased the fiber-matrix inter facial bonding by 72.46%. The lower moisture uptake of the impregnated fiber than the control was qualitatively proven by TGA and FT-IR spectra. In general, the impregnated composites showed better tensile and flexural properties than the controls where 30% fiber loading gave the highest values. It was also observed that MC, WA, thickness swelling (TS) and linear expansion (LE) of impregnated composites were lower than the controls and the moisture excluding efficiency (MEE) and anti-swelling efficiency (ASE) were also increased.